Type 3A free anterolateral thigh chimeric flap based on the Zunyi classification for reconstructing diabetic foot wounds - Zhang, Tianhua; Wu, Xiangkui; Jiang, Lingli; Xiao, Shun’e; Li, Hai; Chen, Wei; Chang, Shusen; Wu, Bihua; Wei, Zairong; Deng, Chengliang (Frontiers in Surgery, 2025)
BackgroundDiabetic foot wounds (DFWs) often present with multilayered tissue loss involving skin, fascia, muscle, and neurovascular structures, posing substantial reconstructive challenges. The Zunyi Classification provides a function-oriented framework for chimeric anterolateral thigh (ALT) flap design. This study aimed to evaluate the clinical efficacy of the Zunyi Type 3A chimeric ALT flap in the reconstruction of complex DFWs.MethodsA retrospective cohort study was carried out involving 28 patients with Wagner grade 2–4 DFWs who underwent reconstruction using a Zunyi Type 3A chimeric ALT flap between June 2021 and June 2024. All flaps were designed based on a single perforator without skin paddle segmentation. Flap composition was tailored to defect characteristics, incorporating combinations of skin, fascia lata, muscle, and sensory nerve. Primary outcomes included flap survival, complication rate, donor-site morbidity, and long-term functional outcome.ResultsAmong the 28 patients with Wagner grade 2–4 DFWs, the most common flap composition was skin + fascia lata + muscle (S + F + M), applied in 17 cases (60.7%). This was followed by skin + muscle + sensory nerve (S + M + N) in 6 cases (21.4%) and skin + fascia lata + sensory nerve (S + F + N) in 5 cases (17.9%). Flap survival was excellent, with 96.4% demonstrating complete viability; one case of partial distal necrosis was managed successfully with debridement and skin grafting. No donor-site complications were observed. During a median follow-up of 13 months (range: 3–30), none of the patients had ulcer recurrence, major infection, or limb-threatening events occurred. Most patients regained satisfactory ambulatory function while preserving limb integrity.ConclusionsThe Zunyi Type 3A chimeric ALT flap offers a reliable, adaptable solution for limb salvage in patients with advanced DFWs. Its capacity to incorporate multiple tissue types in a single, unsegmented design offers effective coverage, structural support, and long-term durability. These findings support broader clinical application of the Zunyi Classification in personalized reconstructive strategies for complex DFWs.